Does tourism cause growth? Evidence from Turkey. Issue 12 (14th October 2016) - Aslan, Alper
Abstract : This paper examines the impact of detailed tourism expenditure on the long-run economic growth by employing Autoregressive Distributed Lag (ARDL) approach and causality test for data set of 2003:1 to 2012:4 in Turkey. The detailed tourism expenditure data are firstly employed for the causality of tourism expenditure on economic growth. The results of the bounds test show that there is a stable long-run relationship between accommodation expenses, transport expenditure, expenditure of sporting activities, sightseeing tour expenditure, clothing–footwear expenditure, gift expenditure and economic growth. The results of the causality test, on the other hand, show that there is a bidirectional causality between accommodation expenses, expenditure of sporting activities, gift expenditure and economic growth and a causal flow from transport expenditure to economic growth which is verified growth-led tourism hypothesis. Results reveal that sightseeing tour expenditure and expenditure of sporting activities are more successful on explaining the long-run growth in Turkey in terms of ARDL coefficients size. This result implies a policy that Turkey needs to invest tourism to gain more especially by focusing accommodation, sightseeing tours, sporting activities and transport infrastructure.